Blastic plasmacytoid dendritic cell neoplasm: a short review and update - Cesare Massone; Giulia Rivoli; Simona Sola; Emanuele Angelucci (Dermatology Reports, 2023)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare hematologic neoplasm (less than 1% of primary cutaneous lymphomas and acute leukemia) with a highly aggressive clinical course and frequent skin, bone marrow and central nervous system (CNS) involvement. Despite a frequent initial response to chemotherapy, relapses with eventual leukemic dissemination are extremely common, leading to poor outcomes and a median overall survival (OS) ranging from 8 to 14 months in first line setting, with standard combination chemotherapy regimens. The skin is the first affected site (in almost 90% of patients) where BPDCN may remain confined for weeks or even months (sanctuary?) until a rapid second step with multiorgan involvement occurs. Therefore, it is of uppermost importance to suspect and recognize early skin lesions and to perform and report a skin biopsy as soon as possible. A multidisciplinary approach with coordination among dermatologists, pathologists and hematologists is definitively crucial in diagnosis and management of BPDCN.